Morphometric and Morphotectonic characteristics of Sürgü and Çardak Faults (East Anatolian Fault Zone) - Musa Balkaya; Hüsnü Serdar Akyüz; Suha Ozden (Journal of Advanced Research in Natural and Applied Sciences)
Within the framework of this study, morphotectonic and structural characteristics of the Sürgü and Çardak faults, the northern branch of the East Anatolian Fault Zone (EAFZ) between Çelikhan and Göksun, were investigated with scrutiny. Further, the results obtained with morphotectonic assessments supported and fortified with a thorough literature review and field studies; thereby, geological features of the region have been analyzed immaculately. The Sürgü and Çardak faults were mapped with special attention to the lithological, structural, and geomorphological features of the study area. Investigations along the Holocene river valleys along the approximately E–W trending Sürgü and Çardak faults evidently indicate that these faults represent sinistral active fault morphology. In terms of morphometric assess-ments, mountain front sinuosity (Smf), the Valley Floor Width-to-Valley Height ratio (Vf) and Stream Length-Gradient Index (SL) were employed along the mountain-piedmont junction and on the drainage network. Recorded Smf values range from 1.21 to 1.48, and average Vf rates are between 0.20 and 1.12, which typically indicate high tectonic activity for the Sürgü and Çardak faults. SL indice exercised along the 10 valleys in the study area, the recorded values vary between 5.8 and 1330.0; besides, the higher anomalies are recorded adjacent to the Sürgü and Çardak faults. Implemented morphotectonic investiga-tions and evaluations indicate that the Sürgü and Çardak faults play a key role in the morphotectonic evolution of the region.